Objeto ambíguo: arte e estética na experiência contemporânea, segundo H. R. Jauss - Mariana Lage Miranda (2007)
The overall objective of the study was to examine the Aesthetic of Reception by Hans Robert Jauss as a theoretical alternative to the modern and contemporary art and aesthetic experience. At first, we analyzed his proposal of a new paradigm of historical investigation of art in order to review the premises which substitute the traditional aesthetic of representation for an aesthetic of reception. We also reviewed the concepts which substantiate his theory. Secondly, we analyzed the authors conviction that modern and contemporary art should be comprehended with a theory that goes beyond the traditional definitions, such as the formal perfection of the work and the contemplative attitude, and formulate the aesthetic activity demanded of the recipient while facing the art after the period of its autonomy. Named by the author as ambiguous object, the contemporary art dissolves the limits between art and extra-artistic reality, turns the viewer into a participant creator of thework, asking him to assume a theoretical attitude in order to determinate the aesthetic qualities of an indeterminate object. Finally, we comprehend the relationship between the autonomy of art and the opening of the work for the participation of the addressee and the demands for a theoretical and reflexive posture.